Leptospira Serovars Ecological Parameters and Water Quality Analysis at Lata Janggut, Jeli, Kelantan, Malaysia: - Mohd Salleh, Siti Nor Aishah; Mohd Amin, Mohamad Faiz; Mohd Zin, Nur Shaylinda; Abu Bakar, Norshila (Journal of Advancement in Environmental Solution and Resource Recovery, 2022)
The number of Leptospirosis cases and deaths in Kelantan from 2009-2015 showed increasing trends with Jeli District had the highest number of fatalities. This study provides information about the ecological parameters of Leptospira sp. at Lata Janggut, i.e., a natural recreational area. In this research, a total of 18 water samples were collected individually from the upstream part of the waterfall, from the shade and direct sun areas for six consecutive weeks from July 26 until August 28 of 2016. Water samples were taken from for the Leptospira sp. availability testing through the morphological characterisation and staining technique. In-situ and ex-situ data were measured as the physical and chemical parameters of water samples. The 16 elements of heavy metal was determined as well. Water quality index (WQI) of the upstream of Lata Janggut was analysed with 64.50 (Class III) and 77.51 (Class II) in the shade and direct sun areas, respectively, according to the WQI value suggested by the Department of Environment (DOE) of Malaysia. Based on the identification, the study area was free from Leptospirosis during the observation period, which correlated with the ecological parameters of Leptospira sp. at Lata Janggut.